2015
DOI: 10.1200/jco.2015.33.3_suppl.59
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of afatinib in patients (pts) with metastatic human epidermal growth factor receptor (HER2)-positive trastuzumab refractory esophagogastric (EG) cancer.

Abstract: 59 Background: Trastuzumab combined with chemotherapy is the standard of care for pts with HER2+ EG cancer. Resistance to trastuzumab clearly emerges in this population. Afatinib, a potent ErbB Family Blocker, induced tumor regression in MSKCC HER2+ patient derived xenografts (PDX). This study assesses safety and preliminary efficacy of afatinib in patients with trastuzumab refractory EG cancer. Methods: Pts with HER2+ (IHC 3+ or FISH>2.0) EG adenocarcinoma, after progression on trastuzumab, received oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…For example, an ongoing Phase II trial is assessing the combination in patients with advanced HER2-positive trastuzumab-refractory esophagogastric cancer (NCT01522768 ; Table 1); preliminary data from this trial indicated that afatinib monotherapy was well tolerated and showed clinical activity in this setting [89]; the addition of trastuzumab to afatinib was mandated in a protocol amendment.…”
Section: Afatinib Plus Her2 Antibodiesmentioning
confidence: 98%
“…For example, an ongoing Phase II trial is assessing the combination in patients with advanced HER2-positive trastuzumab-refractory esophagogastric cancer (NCT01522768 ; Table 1); preliminary data from this trial indicated that afatinib monotherapy was well tolerated and showed clinical activity in this setting [89]; the addition of trastuzumab to afatinib was mandated in a protocol amendment.…”
Section: Afatinib Plus Her2 Antibodiesmentioning
confidence: 98%
“…Preliminary data of a phase II study enrolling patients with metastatic HER2-positive (IHC 3+ or FISH >2.0) esophagogastric cancer with disease progression whilst on a trastuzumab-containing regimen have been recently presented [53, 54] with demonstration of a 40% disease control.…”
Section: Her-2 As a Key Target In Gastric Cancers And Gastroesophageamentioning
confidence: 99%
“…Afatinib, a multi-kinase inhibitor of EGFR, HER2 and HER4, showed signal in a phase II study involving patients with trastuzumab refractory disease 50. An expansion cohort looking at safety and efficacy in combination with trastuzumab is currently recruiting (NCT01522768).…”
Section: Future Directions In Her2 Targetingmentioning
confidence: 99%